2018
DOI: 10.1016/j.radmeas.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Testing single aliquot regenerative dose (SAR) protocols for violet stimulated luminescence

Abstract: Highlights:• Compared two single aliquot regenerative dose protocols for VSL signal • Protocols assessed to minimise recuperation and optimise signal depletion • Partial success in dose recovery of ~400 Gy using post-blue VSL signal • VSL signal gives 50 -79 % underestimation of the expected D e Abstract Basic assumptions of the single aliquot regenerative dose (SAR) protocol are tested using the violet stimulated luminescence (VSL) signal from quartz. The VSL signal is shown to be reduced to a sufficiently lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…All signal intervals of X6888 underestimated the expected minimum D e of 600 Gy by 40-80%. This finding is in agreement with previous research on VSL-SAR, which shows agreement with independent age controls for samples below 200 Gy (Ankjaergaard et al, 2015;Porat et al, 2018), but with severe underestimations of up to 80% reported for samples with expected D e values of 300-8000 Gy (Ankjaergaard et al, 2015(Ankjaergaard et al, , 2016Colarossi et al, 2018;Morthekai et al, 2015). For this reason, a MAAD protocol was tested for the higher-dose samples.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All signal intervals of X6888 underestimated the expected minimum D e of 600 Gy by 40-80%. This finding is in agreement with previous research on VSL-SAR, which shows agreement with independent age controls for samples below 200 Gy (Ankjaergaard et al, 2015;Porat et al, 2018), but with severe underestimations of up to 80% reported for samples with expected D e values of 300-8000 Gy (Ankjaergaard et al, 2015(Ankjaergaard et al, , 2016Colarossi et al, 2018;Morthekai et al, 2015). For this reason, a MAAD protocol was tested for the higher-dose samples.…”
Section: Discussionsupporting
confidence: 92%
“…However, older samples show SAR-derived age underestimation of up to 80% (Ankjaergaard et al, 2015(Ankjaergaard et al, , 2016Colarossi et al, 2018;Morthekai et al, 2015). SAR protocols are in general preferred for OSL dating (Wintle and Murray, 2006), but differences in signal decay and sensitivity changes between the natural and regenerative doses suggest that this approach may be inapplicable to the VSL signal at high doses (>200 Gy; Ankjaergaard et al, 2015Ankjaergaard et al, , 2016Colarossi et al, 2018). In order to overcome these drawbacks, Ankjaergaard et al (2016) suggested the use of a multiple aliquot additive dose (MAAD) protocol to build a dose-response curve (DRC).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In some cases, prior to all IRSL measurements, the aliquots were held at the measurement temperature for a few seconds without IR stimulation in order to reduce the intensity of the residual isothermal luminescence after preheating. In general, test doses between 30 and 50% of the D e values of the sample were used in all pIRIR measurement protocols 7,63 . The suitability of pIRIR dating protocols using pIR 50 IR 290 , pIR 200 IR 290 and pIR 50 IR 170 signals for samples from each loess-paleosol sequence was checked using dose recovery tests on samples bleached in sunlight and/or modern analog samples 64 .…”
Section: Laboratory Measurements Of Luminescence Dating Of Asian Loessmentioning
confidence: 99%
“…Since then, the studies have advanced and improved the methodology, which has been used for dating samples originating from different environments (Galbraith;Roberts, 2012;Murray;Olley, 2002;Tatumi;Rossetti;Soares, 2020;Tsodoulos et al, 2016). Recent studies have tried to extend the upper limit of the optical dating by using violet-stimulated luminescence (VSL), and findings so far are encouraging and indicate this to be a reasonable approach (Ankjaergaard;Wallinga, 2013;Colarossi et al, 2018).…”
Section: Applications Of Thermoluminescence and Optically Stimulated ...mentioning
confidence: 99%